TECHNOLOGICAL OPPORTUNITIES SURVEY OF FOREST SHORT ROTATION PLANTATIONS IN BULGARIA FOR ENERGY BIOMASS PRODUCTION* PART 1: ANALYSIS OF THE PRODUCTION OF ENERGY FROM BIOMASS IN BULGARIA AND PERSPECTIVES FOR CREATING ENERGY PLANTATIONS FROM SHORT ROTATION - Marinov, Konstantin; Gochev, Zhivko; Stoilov, Stanimir (Innovation in Woodworking Industry and Engineering design, 2013)
This report presents some problems on the state and future use of biomass as a renewable source for production of heat and electricity in Bulgaria and Europe. The report covers the potential opportunities of the agricultural lands in Bulgaria for production of energy plantations (SRP) and in particular from forest tree species such as poplar, willow and black locust. A review of their main advantages and disadvantages is made and recommendations for their future development in Bulgaria are presented.